Impact of nursing interventions on the implementation of primary health care policies: A Systematic Review - Awatiful Azza; Zusana A. Sasarari; Etty Komariah Sambas; A. Wardah Muzfah (Jurnal Edukasi Ilmiah Kesehatan, 2025)
Introduction: Primary health care (PHC) is recognized as the foundation of equitable and sustainable health systems. Nursing interventions are essential in translating PHC principles into effective practice. However, limited synthesized evidence exists on the effectiveness of nursing-led initiatives within PHC policy frameworks. This review aimed to evaluate the impact of nursing interventions on the implementation of PHC policies, with the hypothesis that structured nursing interventions enhance health outcomes, policy adherence, and community engagement. Methods: Following the PRISMA guidelines, a systematic search was conducted across PubMed, CINAHL, Scopus, and Cochrane Library for studies published between 2010 and 2025. Eligible studies included randomized controlled trials, quasi-experimental, and observational designs assessing nursing-led interventions in PHC settings. Two reviewers independently performed data extraction and quality appraisal. Due to methodological heterogeneity, a narrative synthesis was employed. Results: A total of studies demonstrated that nursing interventions such as health education, chronic disease management, maternal-child health support, and community empowerment significantly improved service accessibility, patient satisfaction, and adherence to PHC policy objectives. Moreover, community-based nursing initiatives strengthened preventive care delivery and promoted equity in service utilization. Conclusion: The findings confirm that nurses are pivotal in operationalizing PHC policies. Strengthening nursing capacity through training, policy integration, and resource allocation can accelerate progress toward universal health coverage. Further research is needed to establish standardized evaluation frameworks and measure long-term policy impacts of nursing interventions in PHC systems.